A história do livro escolar no Pará: a Grammatica Portugueza de Julio Cezar Ribeiro de Souza e o processo de gramatização do português no Brasil - GOMES, Gabriela de Nazaré Rodrigues. (2025)
The field of study on the history of the book in Brazil has gained significant attention in the Amazon in recent years. The Study Group on the History of Textbooks in the Amazon (GEHLDA), which has been conducting research in this area since 2016, has focused on the history of school books for reading and primary grammars produced in Pará during the period covering the second half of the 19th century and the early 20th century. This research, linked to GEHLDA, aims to understand the importance of Grammatica Portugueza by Julio Cezar Ribeiro de Souza in the process of grammatical standardization of Portuguese in Brazil. To achieve this goal, the study seeks to describe Grammatica Portugueza from a linguistic perspective and analyze linguistic phenomena in the grammar that show signs of the process of grammaticalization of Portuguese in Brazil. The research is primarily based on studies in the field of the History of Linguistic Ideas, as proposed by Auroux (2014) and Colombat, Fournier, and Puech (2017), in addition to the approach on the history of the schoolbook in Pará, based on Duarte (2018). The results show that the Grammatica Portugueza by the Pará intellectual Julio Cezar Ribeiro de Souza, published in 1872, met the requirements set by the province of Pará, which stipulated that primary grammars should adhere to the Portuguese grammatical tradition based on the philosophical conception of language. However, the Pará grammarian did not fully conform to the Portuguese requirements and, in footnotes, presented his critical analysis of the Portuguese language, contributing to the process of grammatical standardization of Portuguese in Brazil.